Didáctica de la física e innovación en el aula - Auzaque, Tatiana (Góndola, enseñanza y aprendizaje de las ciencias, 2008)
We present a new proposal for understanding the Physics Teaching field, imagine the student as an active person, full of questions, able to stand and solve problems of his environment, with need to learn and know, able to do science, and to build scientific knowledge. We start from the fact that today there is no specific and unified theory about physics teaching; however, there are several currents of thought from which curricula, classroom activities and extracurricular activities are designed, which consider in different ways the learning processes, as well as, education meaning and purpose.